Evaluasi Kualitas Sistem Informasi Dosen (SIADO) Oleh Dosen Universitas Brawijaya Dengan Menggunakan Technology Acceptance Model (TAM) Termodifikasi - Anita Dwi Puspitasari; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The use of Lecturer Information System (SIADO) has been so maximized because some users of lecturers have different perspectives on SIADO, such as SIADO's system quality which still get some complaints from users in 2016 and there has been no decision letter from the Rector of mandating the use of SIADO. This study aims to describe how the factors studied on SIADO user acceptance on five variables, namely user characteristics, system quality, top management & IT support, perceived usefulness, and perceived ease of use using descriptive statistical analysis. Data collection techniques using questionnaires that are distributed offline using paper and designed as attractive as possible, the population in the study is a lecturer in UB with 96 samples used. Data from respondents who have been collected through questionnaires processed by seeing whether the data is valid and reliable. After that descriptive statistical analysis is done to know the level of categories owned on each variable that can provide data information based on centralization and dissemination of data, so that obtained average to be categorized. The results show that the five variables get high category on SIADO acceptance, which indicates the user perceives all the good variables to be used as a consideration tool in receiving the system.